Fishbone Diagram as a Catalyst Tool in Teaching Cohesive Ties for Undergraduate Students at the University of Sulaimani - Muhedeen, Asst.Prof.Dr. Bekhal Latif Muhedeen; Hassan, Asst.Prof.Dr. Zana Mahmood Hassan; Faiq, Asst.Prof.Dr. Aseel Muhammad Faiq (Sulaimani Journal for Humanities, 2025)
This quasi-experimental study seeks to identify the impact of the Fishbone Diagram on improving students’ use of cohesive ties. It also seeks to elucidate whether a notable difference exists in their performance before and after the implementation of this visual instructional method. The sample comprises sixty students in their final year of study at the English Department, College of Languages, University of Sulaimani for the academic year (2023-2024). They are divided into experimental and control groups, with the former being instructed using the Fishbone Diagram and the latter receiving conventional teaching instruction. Tests, which are widely recognized as effective and reliable research tools for examining interventions’ impact, are used to collect necessary data and evaluate the impact of the intervention. Both pretest and posttest are conducted to figure out the significant differences observed prior to and following the treatment. The analysis demonstrates that the experimental group outperforms the control group and significantly differs from it in the posttest results, implying the effectiveness of the diagram for teaching cohesive ties and the noticeable positive impact of the intervention on the students’ performance in comparison to the control group.
Keywords: Fishbone (Ishikawa) Diagram; Cohesion; Cohesive Ties; Undergraduate Students